1998
DOI: 10.1074/jbc.273.47.31408
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Signal Transducers and Activators of Transcription 1 and 3 by Leukemia Inhibitory Factor, Oncostatin-M, and Interferon-γ in Adipocytes

Abstract: We have recently demonstrated that signal transducers and activators of transcription (STATs) 1, 3, 5A, 5B, and 6 are expressed in both cultured and native adipocytes. Our current studies have focused on the activation of STATs 1 and 3 by leukemia inhibitory factor (LIF), oncostatin-M (OSM), and interferon-␥ (IFN␥) in 3T3-L1 adipocytes. IFN␥ is shown to be a potent activator of STAT 1 as indicated by both tyrosine phosphorylation and nuclear translocation. However, LIF and OSM, which are potent inducers of STA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 42 publications
2
64
1
Order By: Relevance
“…In contrast, less STAT3 activation by IFN-␥ was found in macrophages from STAT1-deficient versus wild type mice (8). Convincing evidence of STAT3 phosphorylation and binding to promoter elements in the presence of IFN-␥-induced STAT1 activation has been observed in certain human cell types, including VSMCs (15), hematopoietic progenitors (9, 10), neutrophils (10,11), myelocytic leukemia cells (9, 11), adipocytes (35), hepatocytes (36), hepatoma cells (37), neuroblastoma cells (38), and synovial cells (39) but not endothelial cells (23), lymphocytes (11), or monocytes and eosinophils (10). However, IFN-␥ has also been described to dephosphorylate constitutively activated STAT3 in tuberous sclerosis complex-deficient mouse embryonic fibroblasts and human prostate cancer cells (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, less STAT3 activation by IFN-␥ was found in macrophages from STAT1-deficient versus wild type mice (8). Convincing evidence of STAT3 phosphorylation and binding to promoter elements in the presence of IFN-␥-induced STAT1 activation has been observed in certain human cell types, including VSMCs (15), hematopoietic progenitors (9, 10), neutrophils (10,11), myelocytic leukemia cells (9, 11), adipocytes (35), hepatocytes (36), hepatoma cells (37), neuroblastoma cells (38), and synovial cells (39) but not endothelial cells (23), lymphocytes (11), or monocytes and eosinophils (10). However, IFN-␥ has also been described to dephosphorylate constitutively activated STAT3 in tuberous sclerosis complex-deficient mouse embryonic fibroblasts and human prostate cancer cells (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…For example, STAT1 S727 phosphorylation in macrophages is sensitive to SB203580 in stress of LPS responses, but insensitive to this inhibitor in the IFN-g response . Similarly, STAT3 S727 phosphorylation in response to EGF, PDGF, insulin, IL-2, BCR or TCR stimulation is sensitive to PD98059 and, where tested, insensitive to H7, whereas the opposite is true for IL-6 or IFN-a (Chung et al, 1997;Ng and Cantrell, 1997;Stephens et al, 1998;Su et al, 1999). (2) S727 phosphorylation of dierent STATs by signals from the same cell surface receptor can be routed through distinct signaling paths.…”
Section: Kinases and Other Signal Transducers That Participate In Thementioning
confidence: 99%
“…Numerous findings in the last decade have highlighted the differential effects of gp130 cytokines on important adipocyte functions. These studies have shown that adipocytes in vitro and adipose tissue in vivo are responsive to gp130 cytokines (Balhoff and Stephens 1998;Stephens et al 1998;Lagathu et al 2003;Rotter et al 2003;Zvonic et al 2003Zvonic et al , 2004Tenney et al 2005;White et al 2008) and exert differential effects on adipogenesis. To date, no gp130 cytokines have been shown to promote adipogenesis, but as shown in Table 1, several cytokines in this family have been shown to inhibit adipocyte development (Keller et al 1993;Meng et al 2001;Zvonic et al 2003Zvonic et al , 2004Sopasakis et al 2004;Hogan and Stephens 2005;Miyaoka et al 2006;Song et al 2007;White et al 2008).…”
Section: Glycoprotein 130 (Gp130) Cytokinesmentioning
confidence: 99%